Violence against women : a prospective study of women presenting to a South African trauma centre - Dedekind, Britta (Department of Surgery, 2016)
Background - Violence against Women is a major public health issue, and it is universally under reported. Objective - To conduct an injury surveillance of severe or life threatening violent acts against women, to determine the demographics of the injured women and to identify the nature of the perpetrators. Methods - A standardized structured questionnaire administered in an interview conducted on female patients admitted to the Trauma Centre at Groote Schuur Hospital as a result of interpersonal violence. Age, level of education, employment status, housing and substance abuse was recorded.